1994
DOI: 10.1002/neu.480250408
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in adult retinal ganglion cells after axotomy

Abstract: Lesions to the mature mammalian central nervous system cause irreversible degeneration, in which neurons have been previously thought to be passive victims. In this study, axon-lesioned adult rat neurons are shown instead to actively degrade themselves through the process of apoptosis: a programmed type of cell death in which the cellular apparatus is actively involved in the degradation process. To investigate whether retinal ganglion cells of an adult mammal follow an apoptotic type of death when their axons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
152
1
3

Year Published

1996
1996
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 291 publications
(168 citation statements)
references
References 31 publications
12
152
1
3
Order By: Relevance
“…Transection of the ON induces a delayed death of 80 -90% of RGCs within 14 d, starting around day 4 and reaching a maximum on day 7 after axotomy (Eschweiler and Bähr, 1993;Mansour-Robaey et al, 1994). It has been shown that this retrograde cell death can be ascribed to apoptosis (Garcia-Valenzuela et al, 1994;Rabacchi et al, 1994;Isenmann et al, 1997). Caspase-3 (CPP32)-like protease has been identified as an important mediator of apoptotic RGC death in our experimental paradigm (Kermer et al, 1998(Kermer et al, , 1999b.…”
Section: Discussionmentioning
confidence: 84%
“…Transection of the ON induces a delayed death of 80 -90% of RGCs within 14 d, starting around day 4 and reaching a maximum on day 7 after axotomy (Eschweiler and Bähr, 1993;Mansour-Robaey et al, 1994). It has been shown that this retrograde cell death can be ascribed to apoptosis (Garcia-Valenzuela et al, 1994;Rabacchi et al, 1994;Isenmann et al, 1997). Caspase-3 (CPP32)-like protease has been identified as an important mediator of apoptotic RGC death in our experimental paradigm (Kermer et al, 1998(Kermer et al, , 1999b.…”
Section: Discussionmentioning
confidence: 84%
“…In mature mammals, RGCs are unable to regrow injured axons and soon undergo apoptotic death (Garcia-Valenzuela et al, 1994). These well known events are a paradigm of regenerative failure in the CNS and may mimic pathophysiological sequelae that underlie degenerative diseases such as glaucoma (Quigley and Green, 1979;Quigley et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…[42][43][44] One-half of them will degenerate 4 days after optic nerve axotomy, and it rises to about 70% in 1 week and to more than 95% in 2 weeks.…”
Section: Optic Nerve Transectionmentioning
confidence: 99%